Lung Cancer Attracts Greater Stigma than Other Cancer Types in Aotearoa New Zealand. (26th August 2022) - Godward, Jess; Riordan, Benjamin C.; Winter, Taylor; Ashton, John C.; Hunter, John; Scarf, Damian
Abstract : Background . Lung cancer is the leading cause of cancer death in Aotearoa New Zealand, killing over 1, 700 people each year. Despite the burden of lung cancer in Aotearoa New Zealand, the popular press has referred to it as the cancer type that no one talks about. Here, we investigate one factor that may contribute to this state of affairs: lung cancer stigma. Methods . Participants were university students and members of the general public. University students were recruited via an online experiment participation system in 2021. Members of the public were recruited via social media. All participants completed the Cancer Stigma Scale (CSS) for one of five cancer types (lung, cervical, breast, skin, or bowel). The CSS is a 25-item scale with six subscales: awkwardness, avoidance, severity, policy opposition, personal responsibility, and financial discrimination. Results . The mean age of participants was 24.3 (Standard Deviation = 10.4). Data from each subscale were submitted to an analysis of covariance (ANCOVA), with cancer type as a between-participant factor (5: lung, cervical, breast, skin, or bowel) and stigma as the dependent variable. Relative to most other cancer types, people were more likely to avoid someone with lung cancer, view interacting with someone with lung cancer as more awkward, and view people with lung cancer as being responsible for their condition. Conclusion . The Health Research Council of New Zealand recently funded the very first trial of lung cancer screening in Aotearoa New Zealand. The current study suggests that addressing stigma will be essential for the success of such programs, with stigma likely influencing those who engage in such trials.